Prevalence of Stress Urinary Incontinence after Vaginal Hysterectomy in Eastern Nepal - Karki, Gyanendra Man Singh; Pradhan, Tarun; Deo, Amit; Chaulagain, Pujan (Birat Journal of Health Sciences, 2020)
Introduction: Pelvic organ prolapse is reproductive health morbidity in our country and vaginal hysterectomy is one of the most commonly performed surgery. Urinary incontinence is a common problem after hysterectomy. Objective: This study assesses the prevalence of stress urinary incontinence after vaginal hysterectomy and the factors associated for stress urinary incontinence after hysterectomy. Methodology: This is ahospital based descriptive prospective study conducted for a period of 1-year from January 2019 toJanuary 2020. All patients who underwent vaginal hysterectomy for pelvic organ prolapse were included in the study. Datawas recorded in Performa, and patients were followed up with telecommunication after a month of post-operative period regarding occurrence of stress urinary incontinence. Data were statistically analysed for mean, frequency and fisher’s exact test were done to find the association betweenstress urinary incontinence and risk factors. Results: A total of 100 patients were included in the study. Twenty-one (21%) patients complained of post-operative stress urinary incontinence. Stress urinary incontinence was not found to be significantly associated with vaginal hysterectomy, smoking habit, type of work or stage of pelvic organ prolapse. However, it was significantly associated with advancing age. Conclusion: Stress urinary incontinence was significantly associated with advancing age but the association with smoking habit, type of work, stage of pelvic organ prolapse was not statistically significant.